THE EFFECT OF USING SMALL GROUP DISCUSSION TECHNIQUE ON STUDENTS' SPEAKING SKILL AT XI GRADE OF MAS KEPENUHAN - Hidayati, Nur Elmi; Niati, Batdal (JEE (Journal of English Education), 2019)
The purpose of this research was to find out the effect of Small Group Discussion technique on students’ speaking skill in narrative text. This research was conducted in March 2019. The sample was the eleventh grade students of Madrasah Aliyah Swasta (MAS) Kepenuhan. The research method was Experimental research, the number of the sample joined in this research was 40 students. The researcher divided them into two classes,the research post-test only design to find out the effect of Small Group Discussion technique toward on students’ speaking skill. According to the test given, the researcher found that the students’ post test in the independent sample T-test was 0.000 smaller than 0.005 with probabilitas 2 tailed, So, 0.000/2 = 0,000 smaller than α = 0.005, or 0,000 < 0.05. So.Ho rejected. The df 38. It could be concluded that Ha accepted and Ho rejected. It means small group discussion had significant effect on students speaking skill in the narrative text at Eleventh grade students of Mas Kepenuhan.